Stock returns and their distribution: an empirical assessment of the US and Argentina’s stock market for the period 2002/18 - Swoboda, Carlos (2019)
Fil: Swoboda, Carlos. Universidad Nacional de Córdoba. Facultad de Ciencias Económicas; Argentina.